Dietary intake and micronutrient adequacy among adults engaged in agriculture in rural Sri Lanka: findings from a cross-sectional baseline survey - Caroline A Joyce; Bess L Caswell; Aulo Gelli; Sonja Y Hess; Hasara Sitisekara; Christine P Stewart; Xiuping Tan; Renuka Jayatissa; Kalana Peiris; Renuka Silva; Deanna K Olney (Public Health Nutrition)
Abstract